2022
DOI: 10.31635/ccschem.022.202101578
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Synthesis of Covalent Organic Frameworks as Photocatalysts for Hydrogen Peroxide Production

Abstract: Covalent organic frameworks (COFs) are crystalline porous polymers with designable structures and properties. Their crystallization typically relies on trial-and-error involving harsh conditions including organic solvents, presenting significant obstacles for rational design and large-scale production. Here, we present a liquid crystal directed synthesis methodology and its implementation for up to gram-scale production of highly crystalline COFs in water and air. It is compatible to monomers with different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Of note, the metallophthalocyanine-COFs with 5th and 6th period metals (e.g., Pt, Rh, Ag, W, Ta, Mo, Os, and Re) have been predicted based on first-principles density functional theory calculations, 223 but their synthesis still remains blank. 3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanines under alkaline conditions (Fig. 6).…”
Section: Review Articlementioning
confidence: 96%
See 2 more Smart Citations
“…Of note, the metallophthalocyanine-COFs with 5th and 6th period metals (e.g., Pt, Rh, Ag, W, Ta, Mo, Os, and Re) have been predicted based on first-principles density functional theory calculations, 223 but their synthesis still remains blank. 3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanines under alkaline conditions (Fig. 6).…”
Section: Review Articlementioning
confidence: 96%
“…218 In addition to the pyrazine-linked COFs, the piperazinelinked phthalocyanine-COF has also been reported by Huang and co-workers. By Buchwald-Hartwig cross-coupling reaction of nickel(II) 2,3,9,10,16,17,23,24-octaaminophthalocyanine and cobalt(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluorophthalocyanine under solvothermal conditions (dioxane, triethylamine, 120 1C), the piperazine-linked heterometallic NiPc-NH-CoPcF 8 COF was generated. 219 NiPc-NH-CoPcF 8 crystallized in the tetragonal P4/mmm space group, with AA stacking mode, a pore size of 1.1 nm, and an interlayer spacing of 3.6 Å.…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…4.6 μmol h −1 ) 26 (Table S2 †). 27 The high photocatalytic activity of N 0 -COF mainly arises from the promoted light-harvesting ability, increased charge carrier dissociation efficiency, and faster charge transfer, closely related to the D-A structure. To unravel the H 2 O 2 production pathway during photocatalysis, we further conducted the reaction in different atmospheres.…”
Section: Photocatalytic H 2 O 2 Productionmentioning
confidence: 99%
“…In order to produce H 2 O 2 on scale, new photocatalysts have to be developed that fulfil a range of requirements: namely, light absorption profiles that match the solar spectrum, 18 efficient separation of the photogenerated charge carriers, 19 excellent charge transport to the surface and active sites, and high selectivity for surface reactions. 20 Recent studies have shown that metal-free photocatalysts can be superior to the traditional inorganic materials for this aspect, and typical examples include polymeric carbon nitride, [21][22][23][24] covalent heptazine frameworks, 25 covalent organic frameworks (COFs), 26,27 and others. [28][29][30] With respect to inorganic materials, light absorption of meta-free photocatalyst can be readily optimized by rational design of the molecular structure.…”
Section: Introductionmentioning
confidence: 99%